Impact of family-oriented gamification on self-management of people with multiple sclerosis: a mixed-methods study protocol - Arezoo Rasti; Leily Zare; Nahid Dehghan nayeri; Fatemeh Bahramnezhad (BMJ Open)
Introduction Multiple sclerosis (MS) is a chronic disease of the central nervous system that impacts millions worldwide, including individuals in Iran. It primarily affects young people, leading to biopsychosocial challenges with unpredictable symptoms. Self-management is crucial but challenging due to the lack of definitive treatment. New approaches, such as mHealth interventions, particularly gamification, aim to engage patients more effectively. Well-designed gamification may positively impact health behaviours and enhance collaborative care. However, its implementation in the field of MS in Iran is currently limited. So far, some mobile applications have been designed that do not incorporate gamification principles and only focus on one issue. These applications also fail to consider the family caregivers' understanding of the patient’s condition. Therefore, this study aims to investigate the impact of family-oriented gamification on the self-management of Iranian patients with MS.Methods and analysis We propose a mixed-methods study with an exploratory sequential design consisting of a qualitative phase, gamification development and a dual-centre, prospective, single-blinded, parallel-group randomised controlled superiority trial. In the qualitative phase, data will be collected through purposive sampling via semistructured interviews with patients until data saturation is reached. Concurrently, the data will be analysed using conventional content analysis to provide insights into the patients’ self-management challenges. Next, web-based and card gamification will be developed for patients and their families based on the findings of the qualitative phase. Ultimately, the effectiveness of these interventions will be evaluated through a randomised controlled trial. The preliminary literature suggests an initial sample size of 25–30 participants per group for this phase. After enrolling approximately 10 participants, the exact sample size will be recalibrated using G-Power software based on data analysis. Participants will then be randomly assigned to either the intervention or control group in a 1:1 ratio. Allocation concealment will be ensured using mixed block sizes of 2 and 4. The primary outcome, self-management, and the secondary outcome, self-efficacy, will be assessed both before and immediately after the intervention. Furthermore, the usability of the two gamification strategies will be evaluated following the intervention.Ethics and dissemination This study is part of a doctoral thesis approved by the Tehran University of Medical Sciences Research Ethics Board (IR.TUMS.FNM.REC.1401.185, 23 February 2023). Dissemination of findings will occur at the local, national and international levels.Trial registration number IRCT20240116060708N1.